A GC-MS Protocol for the Identification of Polycyclic Aromatic Alkaloids from Annonaceae - Ilya A. P. Jourjine; Carolin Bauernschmidt; Christoph Müller; Franz Bracher (Molecules, 2022)
The Annonaceae are an old family of flowering plants belonging to the order Magnoliales, distributed mainly in tropical regions. Numerous Annonaceae species find ethnobotanical use for curing a broad range of diseases, among them cancer and infections by diverse pathogens. Hence, bioactive natural products from Annonaceae have received considerable interest in drug development. Beyond cytotoxic acetogenins, unique aporphine-derived polycyclic aromatic alkaloids are characteristic constituents of Annonaceae. Among them are unique tri- and tetracyclic aromatic alkaloids like azafluorenones, diazafluoranthenes, azaanthracenes, and azaoxoaporphines. The complex substitution pattern of these alkaloids represents a major challenge in structure elucidation of isolated natural products. Based on a broad spectrum of alkaloids available from our previous work, we present a GC-MS protocol for the identification of over 20 polycyclic aromatic alkaloids from Annonaceae. This collection of data will contribute to the future identification of the metabolite patterns of extracts from Annonaceae as an important source of novel bioactive secondary metabolites.